An Analysis of Students’ Comprehension in Pronouncing English Words by Using Song - Yuneva yuneva; Melati Melati; Elva Utami; siti masitah; Febrilia Syarayani (English Education Study Program Faculty of Teacher Training and Education, 2021)
The aimed of this research was to know the causes of pronunciation errors made by the students and whether the method of learning English prounciation using song can improve the student’s pronouncing English words at SMAN 8 Bengkulu. The method used in this research is a qualitative descriptive. The informants in this research were students from X IPS 1 Data collection is done by interview and quistionnaire. The data obtained were analyzed by reduction of data, presentation of data, and drawing conclusions.The research results show that most of studens of X IPS 1 more interested and understanding if learning English pronunciation using songs because they can follow a native speaker to say English words correctly. The causes error of their English pronunciation is a lack of their confidence when they speaking English and the media can also be an easy or difficult factor for students to learning English pronunciation. It can be concluded that is the right media for students English pronunciation.